2011
DOI: 10.1371/journal.ppat.1002244
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Infection Drives IL-17-Mediated Neutrophilic Allergic Airways Disease

Abstract: A subset of patients with stable asthma has prominent neutrophilic and reduced eosinophilic inflammation, which is associated with attenuated airways hyper-responsiveness (AHR). Haemophilus influenzae has been isolated from the airways of neutrophilic asthmatics; however, the nature of the association between infection and the development of neutrophilic asthma is not understood. Our aim was to investigate the effects of H. influenzae respiratory infection on the development of hallmark features of asthma in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 70 publications
9
150
0
Order By: Relevance
“…In each instance, a single drop of blood was smeared onto a microscope glass slide, which was then stained with H&E. The differential cell populations were enumerated based on their morphology, as described previously (32).…”
Section: Histochemistry and Enzyme Cytochemistry Evaluation Of The MCmentioning
confidence: 99%
“…In each instance, a single drop of blood was smeared onto a microscope glass slide, which was then stained with H&E. The differential cell populations were enumerated based on their morphology, as described previously (32).…”
Section: Histochemistry and Enzyme Cytochemistry Evaluation Of The MCmentioning
confidence: 99%
“…Other studies have shown that blocking membrane-bound IL-6R, with anti-IL-6R Ab induces Tregs and attenuates AAD (38). Because the Th17 cell cytokines IL-25 and IL-17 contribute to the inflammatory milieu in AAD (13,39), and these factors were suppressed by treatment (Fig. 4J, 4K), T+P may be effective in suppressing Th17-mediated asthma pathogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Airway hyperresponsiveness AHR was assessed as described previously (13)(14)(15). Briefly, anesthetized and tracheotomized mice were cannulated and connected to inline aerosol and ventilator apparatus.…”
Section: T Cell Cytokine Releasementioning
confidence: 99%
“…In addition, IL-17A was described to affect airway inflammation through several pathways. IL-17A induces indirect activation and infiltration of neutrophils into the airways, partially through induction of KC expression in structural cells of the airways (38,39). Furthermore, IL-17A seems also to be able to amplify Th2 immune responses (40,41).…”
Section: Discussionmentioning
confidence: 99%